Effect of Different Levels of Pruning on Quality of Custard Apple (Annona squmosa L.) - Kadam, S. R.; Dheware, R. M.; Urade, P. S. (International Journal of Bio-resource and Stress Management, 2018)
Pruning and defoliation are essential operations for inducing off-season flowering and fruiting to yield better quality and quantity of fruits in custard apple. A study was undertaken to investigate the effect of different levels of pruning on growth and quality of custard apple (Annona squamosa L.), cultivar Dharur-6 of eight years old plants spaced at 4×4 m2. studied at custard apple, Research Station, Ambajogai, district Beed during the year 2016–2017. The data has been statistically analyzed by using Randomized Block design. In this experiment, six pruning treatments (5 cm, 10 cm, 15 cm, 20 cm, 25 cm and control) were taken after harvesting of previous year fruits. Shoot emergence was found earlier, in pruned trees as compared to unpruned trees. The statistical analysis revealed that, the treatment Pruning at 20 cm shows maximum weight of fruit (263 g), weight of pulp (110.7) and weight of peel (131.23 g) ware recorded. Maximum total soluble solid (23.80%) was recorded in the treatment pruning at 20 cm. Maximum reducing sugar (18.50%) was recorded in treatment pruning at 15 cm. Significantly maximum non-reducing sugar 1.88% was observed in treatment Pruning at 15 cm. Significantly maximum total sugar 20.38% was recorded in the treatment Pruning at 15 cm. Hence, it is therefore suggested that treatment pruning at 20 cm can be used to maintain growth and quality of custard apple.